Possible cardiotoxicity associated with low‐dose doxorubicin during chemotherapy in a ring‐tailed lemur (Lemur catta) with multicentric lymphoma. Issue 1 (3rd January 2022) - Stringer, Elizabeth; Thamm, Douglas; Melendez, Giselle; Han, Sushan
Abstract: This case report describes an 18‐year‐old, male, ring‐tailed lemur ( Lemur catta ) diagnosed with multicentric lymphoma and leukaemia treated with a modified 16‐week cyclophosphamide, doxorubicin, vincristine, and prednisolone protocol, using anaesthesia for the intravenous chemotherapy administration of vincristine and doxorubicin, in addition to daily oral prednisolone and monthly oral cyclophosphamide. This regimen was repeated four times and modified to a 3‐week protocol with removal of doxorubicin for one additional cycle. There was initial decrease in peripheral node diameter without change of leukaemia. The lemur tolerated treatments well, remaining socially active within the troop, with normal appetite and demeanour. The lemur gradually developed azotaemia and then declined rapidly in the fifth month after diagnosis, ultimately becoming hyporexic, losing weight, and was humanely euthanased. At postmortem examination, multicentric lymphoma was as noted clinically with severe myocardial degeneration and fibrosis that included histological features similar to doxorubicin cardiotoxicity, as described in humans and other species.